Selection of maize lines resistant to drought stress using PEG 6000 in the vegetative phase - Arifin, Nur Iman; Suhartono, Suhartono; Amzeri, Achmad; Umam, Ahmad Syaiful (Agrovigor, 2025)
Selection of maize lines for drought stress is the initial step in developing maize varieties with high production characteristics and resistance to drought stress. The research aims to determine the characteristics of maize lines in the vegetative phase and to select for resistance of maize lines in the vegetative phase using PEG 6000. The research used a Randomized Complete Block Design (RCBD), which was arranged factorially with three replications and two treatments. The number of treatments in this study was 40 treatment combinations, so there were 120 experimental units. Factor I was genotype, and factor II was the giving of PEG-6000 solution. All maize lines were planted in polybags measuring 20 x 20 cm. There are two levels of PEG 6000 solution treatment: 0% concentration (optimum condition) and 10% concentration, which is equivalent to -0.19 Mpa (drought stress condition)  (Mexal et al., 1975). When the plants are 10 days after planting (DAP), drought stress is applied using a 10% concentration of PEG 6000 solution. The observed characters were plant height, root length, leaf area, leaf chlorophyll, plant wet weight, and plant dry weight.  The research results showed that drought stress treatment mostly reduced the character values of plant height, root length, leaf area, leaf chlorophyll, plant wet weight, and plant dry weight. All tested lines showed significant differences in all tested characters against optimum condition treatments and drought stress. The lines resistant to drought stress were G4, G9, G11, G13, G14, G15, G16, G17, and G19.